Pilot scale intensification of rubber seed (Hevea brasiliensis) oil via chemical interesterification using hydrodynamic cavitation technology - Bokhari, A. (Elsevier Ltd, 2017)
Chemical interesterification of rubber seed oil has been investigated for four different designed orifice devices in a pilot scale hydrodynamic cavitation (HC) system. Upstream pressure within 1–3.5 bar induced cavities to intensify the process. An optimal orifice plate geometry was considered as plate with 1 mm dia hole having 21 holes at 3 bar inlet pressure. The optimisation results of interesterification were revealed by response surface methodology; methyl acetate to oil molar ratio of 14:1, catalyst amount of 0.75 wt. and reaction time of 20 min at 50 °C. HC is compared to mechanical stirring (MS) at optimised values. The reaction rate constant and the frequency factor of HC were 3.4-fold shorter and 3.2-fold higher than MS. The interesterified product was characterised by following EN 14214 and ASTM D 6751 international standards. © 2017 Elsevier Ltd